Ensino de Português nos Estados Unidos: uma compilação - Bagio Furtoso, Viviane; J. Rivera, Serena (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
As renovations and expansions within the area of Portuguese for Speakers of Other Languages continue to flourish, an increasing demand for the subject among foreigners and, concurrently, its instruction in various contexts have also been noted. Rooted in an interest in exploring this growth, this article offers a compilation of recently published research with a focus on the history, development, and current perspectives regarding the teaching of Portuguese in universities within the United States. Through the examination of recently published works, this article aims to contribute to the mapping of the instruction and expansion of Portuguese as a Foreign Language in universities throughout the United States while bringing together salient information on the subject that oftentimes when isolated forces a delay in the retrieval of and reflection on instruction and research within this particular area.